Innovative feedstocks for optimal mass production of the edible long-horned grasshopper, Ruspolia differens - Margaret, Kababu; Collins, Mweresa K.; Subramanian, Sevgan; Egonyu, James P.; Nakimbugwe, Dorothy; Ssepuuya, Geoffrey; Faith, Nyamu; Ekesi, Sunday; Tanga, Chrysantus M. (Frontiers in Physiology, 2022)
The edible long-horned grasshopper Ruspolia differens Serville (Orthoptera:Tettigoniidae) is a highly nutritious food source consumed in over 20 African countries. Its occurrence is highly seasonal, and wild harvesting is carried out using locally designed and inefficient light traps, thus limiting sustainable utilization as an important food source. To ensure year-round production and availability of R. differens, we evaluated the effects of low-cost and affordable diets based on agricultural by-products on their growth performance, survival, fecundity, and longevity. A total of four diets with varying ratios of agricultural by-products were evaluated: Diet 1 [33.3% maize bran (MB) + 33.3% wheat bran (WB) + 33.3% Moringa oleifera leaf powder (MOLP)], Diet 2 [25% MB + 25% WB + 25% MOLP + 25% shrimp powder (SP)], Diet 3 [20% MB + 20% WB + 20% MOLP + 20% SP + 20% soya bean meal], and Diet 4 (“control”—routinely used diet). The grasshoppers were subjected to the diets from the 1st nymphal instar (24-h-old stages) through adult stages until death. Diet 3 had the highest crude protein content (28%) and digestibility (74.7%). R. differens fed Diet 3 had the shortest development time (57 days) [p < 0.001], highest survival (87%) [p < 0.001], and maximum longevity (89 days) [p = 0.015] and fecundity (247 eggs/female) [p = 0.549] across the various diets. Female survival rate (59%) on Diet 3 was significantly higher compared to the males (41%). The adult female weight gain was significantly higher compared to males fed on different diets. Percentage hatchability of eggs was not significantly different when females were fed Diet 3 and Diet 2. There was a significantly positive correlation between longevity and fecundity of R. differens reared on Diet 2 and 3. These diets could be further optimized and fine-tuned for improved cost-effective mass production of R. differens continent-wide to reduce dependence on erratic and poor seasonal harvest during swarms.